Kinetics and symmetry of divisions of hematopoietic stem cells - Ho, Anthony Dick (Experimental hematology, 2005)
To fulfill the dual abilities to self-renew and to differentiate into cells of multiple lineages, stem cells must undergo, at some stage, asymmetric divisions to generate cells to sustain the stem cell pool as well as the various progeny cells of the distinct lineages. A central question in developmental biology is how a single cell can divide to produce two progeny cells that adopt different fates. Different daughter cells can theoretically arise by uneven distribution of determinants upon cell division, i.e., due to intrinsic factors, or become different upon subsequent exposure to environmental signals, i.e., due to extrinsic factors. Recent advances in the understanding of stem cell biology in Drosophila and murine models have served as a model for hematopoietic stem cell (HSC) development. Provided with advances in molecular and cellular biology, we have gained insight into the mechanisms governing self-renewing asymmetric divisions of primitive HSC. Direct contact with cellular determinants in the niche has been shown to play an essential role in the balance between self-renewing asymmetric division versus differentiation. Identification of the molecular interactions between stem cells and their niche will lead to an understanding of the mechanisms controlling the long-term destiny of stem cells. Ultimately, molecular signals triggered by adhesion and junction complexes are probably responsible for the specific adoption of differentiation pathways.
Gesehen am 03.12.2021